A hydrogel-based recyclable composite photocatalyst and a preparation method thereof

CN122538245BActive Publication Date: 2026-10-16LUDONG UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611048171.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-15
Publication Date
2026-10-16
Estimated Expiration
2046-07-15

AI Technical Summary

Technical Problem

水凝胶孔道微环境中的酸、碱调控不易实现,但对温度的调控相对容易

Benefits of technology

[0011] The advantages of this invention are as follows: The hydrogel-based composite photocatalyst Gel@CQDs prepared by this invention exhibits excellent photocatalytic degradation performance on organic dyes such as eosin Y, methyl orange, methylene blue, rhodamine B, and malachite green. Furthermore, it is easily recyclable, reusable, and exhibits good stability and catalytic performance, providing a good strategy for treating wastewater containing organic dyes. In addition, the preparation method of the hydrogel-based composite photocatalyst Gel@CQDs provided by this invention uses readily available and inexpensive raw materials, employs mild reaction conditions, is easy to control, and has a simple synthetic route, making it suitable for large-scale preparation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122538245B_ABST
    Figure CN122538245B_ABST
Patent Text Reader

Abstract

The application discloses a hydrogel-based recyclable composite photocatalyst and a preparation method thereof, and belongs to the technical field of catalysts. The preparation method of the hydrogel-based recyclable composite photocatalyst comprises the following steps: taking core-shell fruit and vegetable residues as raw materials, doping nitrogen elements, and synthesizing carbon quantum dots by using a hydrothermal method; dissolving acrylamide, hydroxyethyl methacrylate, glycidyl methacrylate, N, N-methylene bisacrylamide and potassium persulfate in deionized water, adding the carbon quantum dots, and uniformly mixing; loading the mixed solution into a mold, sealing, heating in a 60 DEG C water bath for 20 min, then increasing the temperature to 85 DEG C and reacting for 6 h; and soaking and washing the obtained composite hydrogel with deionized water. The hydrogel-based composite photocatalyst prepared by the application has excellent photocatalytic degradation performance on various organic dyes, and is easy to recycle, has good stability and catalytic performance in repeated use.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a catalyst and its preparation method, specifically to a hydrogel-based recyclable composite photocatalyst and its preparation method, belonging to the field of catalyst technology. Background Technology

[0002] Organic dyes are widely used in industries such as rubber, pigments, and textiles. They are diverse, highly water-soluble, and difficult to biodegrade. Common methods for removing organic dyes from aqueous media include adsorption, membrane filtration, biological treatment, ion exchange, and chemical oxidation. Compared to these methods, photocatalysis has attracted much attention due to its advantages such as green energy use, high catalytic efficiency, simple operation, and non-toxic degradation products. Various photocatalysts, such as metal oxides, metal sulfides, and inorganic semiconductors, have been used in the photocatalytic degradation of organic dyes. Among them, carbon quantum dots are a commonly used photocatalyst, possessing advantages such as rapid electron-hole pair generation, excellent electron transport performance, good thermal stability, non-toxicity, excellent light absorption, and ease of acquisition, demonstrating wide applicability in the treatment of wastewater containing organic dyes. Carbon quantum dots synthesized using doping methods can increase their catalytic activity and introduce abundant active functional groups on their surface, facilitating further chemical modification. However, several challenges remain in this field. In most studies, efficient removal of organic dyes typically requires large doses of catalyst. Furthermore, catalyst recovery experiments are hampered by the small size (nanoscale) of carbon quantum dots, leading to significant catalyst loss and reduced catalytic efficiency after repeated use. Residual catalyst also causes secondary pollution of the aqueous solution. To achieve low catalyst loading and easy recovery, numerous attempts have been made, such as loading photocatalyst particles onto two-dimensional substrates like glass fibers and titanium meshes. However, most of the substrates used in these studies are opaque and insoluble, which negatively impacts efficient light absorption and catalytic efficiency.

[0003] Hydrogels are highly hydrophilic organic materials with a three-dimensional cross-linked network structure. They have advantages such as low preparation cost, large specific surface area, high transmittance, good adsorption and easy recycling. The rich mass transfer channels make them ideal carriers for photocatalysts. In addition, loading photocatalysts into hydrogels has other advantages, such as uniform distribution of photocatalysts, reduced agglomeration and a certain degree of reduction in electron-hole recombination. Currently, the commonly reported methods for using hydrogel-loaded photocatalysts to treat wastewater containing organic dyes mainly include two types of composite catalyst preparation: (1) loading pre-prepared photocatalyst particles into hydrogel channels. For example, Nguyen et al. fixed TiO2 nanoparticles in a cellulose hydrogel matrix, which could photocatalytically degrade nearly 90% of organic dyes within 180 min. (2) synthesizing photocatalyst particles directly in situ within hydrogel channels. For example, Zhang Lina et al. synthesized β-FeOOH catalyst particles in the pores of cellulose-based hydrogels, which showed good removal performance in the adsorption and degradation of methylene blue. However, the hydrogel composite catalysts prepared by physical deposition or electrostatic / hydrogen bonding are not firmly bonded to the hydrogel framework. During recycling, the catalyst particles are prone to detachment, resulting in a significant decrease in catalytic efficiency after 3-5 cycles (for example, in the report by Nguyen et al., the degradation efficiency was only maintained at 80.0% after 5 cycles).

[0004] Carbon quantum dots (QDs) prepared by hydrothermal synthesis typically retain polar functional groups such as hydroxyl and carboxyl groups on their surface. During synthesis, dopants can be added to introduce functional groups such as thiol and amino groups, creating conditions for further catalyst modification. Commonly used dopants are small-molecule nitrogen- and sulfur-containing compounds, which are prone to decomposition at high temperatures and whose doping ratios are difficult to control. Doping with nitrogen- and sulfur-containing ordered polymers can effectively solve these problems. These polar groups on the surface of carbon QDs can form covalent bonds with reactive functional groups such as epoxy and amide groups pre-introduced in the hydrogel framework through nucleophilic substitution, nucleophilic attack ring-opening, and click chemistry reactions, enhancing their structural stability. The content and distribution of surface groups on carbon QDs also have a significant impact on their modification. Too many polar group reaction sites can cause the surface to be covered by the hydrogel framework structure, reducing the contact area with the degraded substances and lowering catalytic performance. Too few groups make modification reactions difficult, preventing the carbon QDs from stably connecting to the hydrogel framework. Among them, core-shell biomass (such as peanut shells and walnut shells) can be used as the main carbon source for carbon quantum dot synthesis due to their high lignin / cellulose content, and the prepared carbon quantum dots have a uniform distribution and moderate number of polar groups on their surface. Secondly, the effective activation temperature of commonly used initiators in hydrogel synthesis, such as potassium persulfate, ammonium persulfate, and azobisisobutyronitrile, is usually between 50-60℃. Excessive temperature will cause polymerization to be too rapid, significantly affecting the structural regularity of the hydrogel channels. Furthermore, the aforementioned nucleophilic substitution and nucleophilic attack ring-opening reactions require acidic, alkaline, or high-temperature conditions to occur fully. While acid and alkaline control of the microenvironment of hydrogel channels is difficult to achieve, temperature control is relatively easy. Therefore, by precisely designing the types and ratios of hydrogel synthesis monomers and covalently linking carbon quantum dots to the hydrogel framework via a one-pot, two-step synthesis method with precise temperature control in two stages, a hydrogel composite catalyst can be prepared. This method is expected to simplify the synthesis steps, improve the structure and catalytic stability of the composite catalyst, and achieve efficient and low-cost photocatalytic degradation and removal of organic dyes from industrial wastewater while retaining the high catalytic activity of carbon quantum dots.

[0005] In conclusion, developing a composite photocatalyst that exhibits high degradation efficiency for organic dyes, low synthesis cost, stable structure, and easy recovery is of great significance in the treatment of wastewater containing organic dyes. Summary of the Invention

[0006] To address the shortcomings of existing technologies, the present invention aims to provide a hydrogel-based composite photocatalyst that exhibits high degradation efficiency for organic dyes, stable structure, and easy recyclability, and also provides a method for preparing the hydrogel-based composite photocatalyst with low synthesis cost.

[0007] To achieve the above objectives, the present invention adopts the following technical solution: A method for preparing a hydrogel-based recyclable composite photocatalyst includes the following steps: (1) Using shelled fruit and vegetable residues as raw materials, nitrogen elements are doped by adding a polymer nitrogen source and carbon quantum dots are synthesized by hydrothermal method; (2) Dissolve acrylamide, hydroxyethyl methacrylate, glycidyl methacrylate, N,N-methylenebisacrylamide and potassium persulfate in deionized water in a ratio of 20 mmol: 0.5 mmol: 0.8 mmol: 0.08 mmol: 0.03 mmol: 10 mL, add carbon quantum dots and mix well; (3) Pour the mixture into a mold, seal it, heat it in a 60°C water bath for 20 min, and then raise the temperature to 85°C and react for 6 h; (4) The obtained composite hydrogel is soaked and washed with deionized water.

[0008] Preferably, in step (1), the shelled fruit and vegetable residue is cherry pit, walnut shell, peach pit, mango pit, coconut shell, durian shell, peanut shell or melon seed shell; the polymer nitrogen source is polyacrylonitrile, polyacrylamide, polymethacrylamide or polyvinylpyridine; the hydrothermal reaction temperature is 200℃ and the reaction time is 16h.

[0009] Preferably, in step (4), the deionized water is replaced every 8 hours for a total of 3 times.

[0010] A hydrogel-based recyclable composite photocatalyst was prepared by the aforementioned method.

[0011] The advantages of this invention are as follows: The hydrogel-based composite photocatalyst Gel@CQDs prepared by this invention exhibits excellent photocatalytic degradation performance on organic dyes such as eosin Y, methyl orange, methylene blue, rhodamine B, and malachite green. Furthermore, it is easily recyclable, reusable, and exhibits good stability and catalytic performance, providing a good strategy for treating wastewater containing organic dyes. In addition, the preparation method of the hydrogel-based composite photocatalyst Gel@CQDs provided by this invention uses readily available and inexpensive raw materials, employs mild reaction conditions, is easy to control, and has a simple synthetic route, making it suitable for large-scale preparation. Attached Figure Description

[0012] Figure 1 This is a SEM image of the hydrogel-based composite photocatalyst Gel@CQDs, with a scale bar of 100 μm; Figure 2 This is a SEM image of the hydrogel-based composite photocatalyst Gel@CQDs-60, with a scale bar of 100 μm. Figure 3 This is a SEM image of the hydrogel-based composite photocatalyst Gel@CQDs-85, with a scale bar of 100 μm. Figure 4These are images of hydrogel-based composite photocatalysts Gel@CQDs and Gel@CQDs-60 under ultraviolet light irradiation. The one on the left is Gel@CQDs-60, and the one on the right is Gel@CQDs. Figure 5 These are actual images of hydrogel-based composite photocatalysts Gel@CQDs and Gel@CQDs-60 under natural light. The one on the left is Gel@CQDs-60, and the one on the right is Gel@CQDs. Figure 6 These are FT-IR images of carbon quantum dots (CQDs), blank hydrogel (Gel), and hydrogel-based composite photocatalyst (Gel@CQDs). Figure 7 This is the UV-Vis diffuse reflectance spectrum of the hydrogel-based composite photocatalyst Gel@CQDs; Figure 8 It is based on Figure 7 The calculated bandgap diagram is shown. Figure 9 This is the Mott-Schottky curve of the hydrogel-based composite photocatalyst Gel@CQDs; Figure 10 The figure shows the calculated removal rates of eosin Y by the hydrogel-based composite photocatalysts Gel@CQDs, Gel@CQDs-60, and Gel@CQDs-85. Figure 11 The graph shows the calculated removal rate of eosin Y by the hydrogel-based composite photocatalyst Gel@CQDs after each cycle. Figure 12 The results show the calculated removal rates of different organic dyes by the hydrogel-based composite photocatalyst Gel@CQDs. Detailed Implementation

[0013] The present invention will be further described below with reference to the accompanying drawings of the embodiments, but the present invention is not limited to the following embodiments. Unless otherwise specified, the methods described are conventional methods. Unless otherwise specified, the raw materials are all available from publicly available commercial sources.

[0014] I. Preparation of hydrogel-based composite photocatalysts

[0015] Example 1

[0016] 1. Preparation of carbon quantum dots (CQDs) Using shelled fruit and vegetable residues as raw materials, nitrogen was doped with a polymer nitrogen source, and CQDs with excellent photocatalytic performance and a suitable number of surface functional groups were synthesized via a hydrothermal method. Specifically: Dry the cherry pits, grind them, and sieve them to obtain a powder of 100-120 mesh. Weigh 1.0 g of cherry pit powder and 0.05 g of polyacrylonitrile with a molecular weight in the range of 4000 Da-4500 Da, disperse them in 60 mL of deionized water, and transfer the mixture to a 100 mL reaction vessel. Seal the reaction vessel and react it in a preheated oven at 200 °C for 16 h. After the reaction is complete, centrifuge the reaction solution at 10000 r / min for 20 min. Filter the supernatant through a 0.22 μm filter membrane, and place the filtrate into a dialysis bag with a molecular weight of 5000 Da for dialyzing in deionized water. Change the deionized water every 12 h, for a total of 3 times. After dialyzing, store the carbon quantum dot solution at 4 °C.

[0017] Cherry pits are characterized by their high lignin and cellulose content. Walnut shells, peach pits, mango pits, coconut shells, durian shells, peanut shells, melon seed shells, and other shelled fruit and vegetable residues also have the same characteristics, so they can all be used as substitutes for cherry pits in the preparation of CQDs.

[0018] Polyacrylonitrile is a carbon-chain polymer containing nitrogen. Polyacrylamide, polymethacrylamide, and polyvinylpyridine are also carbon-chain polymers containing nitrogen, so they can all replace polyacrylonitrile in the preparation of CQDs.

[0019] 2. Preparation of hydrogel-based composite photocatalysts (Gel@CQDs) A low-cost, stable, and high-performance hydrogel-based composite photocatalyst was prepared using a segmented temperature-controlled method. Specifically: Weigh 20 mmol acrylamide, 0.5 mmol hydroxyethyl methacrylate, 0.8 mmol glycidyl methacrylate, 0.08 mmol N,N-methylenebisacrylamide, and 0.03 mmol potassium persulfate, dissolve them in 10 mL of deionized water, and add 2 mL of the carbon quantum dot solution prepared in step 1. Mix well. Measure 0.5 mL of the mixture into each of 1 cm (length) × 1 cm (width) × 0.5 cm (height) silicone molds, seal them, and heat in a 60°C water bath for 20 min to synthesize a hydrogel. Then, raise the temperature to 85°C and react for 6 h. Wash the resulting composite hydrogel with deionized water, changing the deionized water every 8 h for a total of 3 times. Store the resulting hydrogel-based composite photocatalyst in deionized water and label it Gel@CQDs.

[0020] As a control, a blank hydrogel was prepared. Specifically, 20 mmol of acrylamide, 0.5 mmol of hydroxyethyl methacrylate, 0.8 mmol of glycidyl methacrylate, 0.08 mmol of N,N-methylenebisacrylamide, and 0.03 mmol of potassium persulfate were weighed and dissolved in 12 mL of deionized water, and mixed thoroughly. 0.5 mL portions of the mixture were then poured into separate silicone molds, sealed, and the blank hydrogels were prepared using the same method as above. This blank hydrogel is denoted as Gel.

[0021] Comparative Example 1 Hydrogel-based composite photocatalysts were prepared in a one-step, isothermal process. Specifically: Weigh 20 mmol acrylamide, 0.5 mmol hydroxyethyl methacrylate, 0.8 mmol glycidyl methacrylate, 0.08 mmol N,N-methylenebisacrylamide, and 0.03 mmol potassium persulfate, dissolve them in 10 mL of deionized water, add 2 mL of the carbon quantum dot solution prepared in Example 1, and mix thoroughly. Measure 0.5 mL of the mixture into 1 cm × 1 cm × 0.5 cm silicone molds, seal, and heat in a 60 °C water bath for 6 h 20 min to synthesize a hydrogel. Wash the obtained composite hydrogel with deionized water, changing the deionized water every 8 h for a total of 3 times. Store the obtained hydrogel-based composite photocatalyst in deionized water, labeled Gel@CQDs-60.

[0022] Comparative Example 2 The method is basically the same as that described in Comparative Example 1, except that the water bath temperature is 85°C. The obtained hydrogel-based composite photocatalyst was stored in deionized water and denoted as Gel@CQDs-85.

[0023] II. Material Characterization 1. Scanning electron microscopy test Scanning electron microscopy (SEM) can characterize the surface morphology of materials. The hydrogel-based composite photocatalysts Gel@CQDs, Gel@CQDs-60, and Gel@CQDs-85 prepared earlier were freeze-dried, broken in the middle, and the cross-sectional morphology of the samples was observed.

[0024] Scanning electron microscope (SEM) images of the hydrogel-based composite photocatalysts Gel@CQDs, Gel@CQDs-60, and Gel@CQDs-85 are shown below. Figure 1 , Figure 2 and Figure 3 .

[0025] from Figures 1 to 3It can be seen that Gel@CQDs has a rich pore structure with a pore size of about 20μm-30μm (providing abundant reaction sites for the entry and degradation of organic dyes); the morphology of Gel@CQDs-60 is similar to that of Gel@CQDs; the skeleton of Gel@CQDs-85 is significantly thicker, the pores are smaller, and the number of pores is less.

[0026] Therefore, Gel@CQDs and Gel@CQDs-60 were used for further testing.

[0027] 2. Ultraviolet light irradiation test Ultraviolet (UV) light irradiation tests can characterize the fluorescence properties of materials. Images of the hydrogel-based composite photocatalysts Gel@CQDs and Gel@CQDs-60 prepared previously under UV irradiation are shown below. Figure 4 .

[0028] from Figure 4 As can be seen, Gel@CQDs exhibit brighter fluorescence properties under ultraviolet light irradiation.

[0029] The physical images of the hydrogel-based composite photocatalysts Gel@CQDs and Gel@CQDs-60 prepared above under natural light irradiation are shown below. Figure 5 .

[0030] from Figure 5 As can be seen, under natural light, Gel@CQDs-60 is basically colorless and transparent, while Gel@CQDs is pale yellow, indicating a significantly higher carbon quantum dot loading (which shows that stage temperature control has a huge promoting effect on the stable loading of carbon quantum dots in the synthesis of hydrogel-based composite photocatalysts).

[0031] Therefore, Gel@CQDs were used for further testing.

[0032] 3. Infrared testing Infrared spectroscopy can characterize and verify the structure of materials. The Fourier transform infrared (FT-IR) spectra of the previously prepared carbon quantum dots (CQDs), blank hydrogel (Gel), and hydrogel-based composite photocatalyst (Gel@CQDs) are shown below. Figure 6 .

[0033] from Figure 6 It can be seen from this that at 3200cm -1 -3600cm -1 The vibrational peaks within the range are the stretching vibrations of OH and NH on Gel@CQDs. At 3000 cm⁻¹... -1 -2835cm -1 The peak at 1715 cm⁻¹ is related to the CH stretching vibrations of the methyl (-CH₃) and methylene (-CH₂) groups.-1 The peak at 1611 cm⁻¹ is related to the stretching vibration of the C=O group of the ester in the monomer. -1 -1600cm -1 and 1437cm -1 -1450cm -1 The characteristic peak at that location is caused by the bending vibrations of the CO and NH amide groups.

[0034] 4. Ultraviolet-Visible Diffuse Reflectance Test UV-Vis diffuse reflectance testing can characterize the light absorption properties of materials. The UV-Vis diffuse reflectance spectra of the previously prepared hydrogel-based composite photocatalyst Gel@CQDs are shown below. Figure 7 .

[0035] from Figure 7 As can be seen, Gel@CQDs have a strong absorption peak at 280nm and still have a certain absorption intensity in the visible light region >400nm.

[0036] The band gap characterizes the optical properties of a material (determining the material's absorption and emission thresholds for light). According to... Figure 7 The calculated band gap of the hydrogel-based composite photocatalyst Gel@CQDs was plotted. The results are shown below. Figure 8 The calculated band gap of this Gel@CQDs is 3.35 eV.

[0037] 5. Mott-Schottky Test Mott-Schottky tests can characterize the electrochemical properties of materials. The Mott-Schottky curves of the previously prepared hydrogel-based composite photocatalysts Gel@CQDs are shown below. Figure 9 .

[0038] Processing the Mott-Schottky curves at different scan rates reveals that the conduction band potential (CB) of Gel@CQDs is -0.18V. Calculations (using the formula: E(VB) - E(CB) = band gap) show that the valence band potential (VB) is 3.17V.

[0039] III. Photocatalytic Degradation Performance of Hydrogel-Based Composite Photocatalysts Gel@CQDs, Gel@CQDs-60, and Gel@CQDs-85 1. Degradation efficiency of eosin Y Using a 100 mg / L aqueous solution of eosin Y as a sample, the previously prepared hydrogel-based composite photocatalysts Gel@CQDs, Gel@CQDs-60, or Gel@CQDs-85 (1 cm × 1 cm × 0.5 cm) were added to the sample. One piece of hydrogel-based composite photocatalyst was added to every 10 mL of sample. Catalytic degradation was carried out at room temperature under sunlight irradiation. After 80 min, the hydrogel-based composite photocatalyst was removed from the sample, the concentration of eosin Y in the sample was detected, and the removal rate of eosin Y was calculated.

[0040] The calculated removal rates of eosin Y by the hydrogel-based composite photocatalysts Gel@CQDs, Gel@CQDs-60, and Gel@CQDs-85 are shown in the figure. Figure 10 .

[0041] from Figure 10 It can be seen that, compared with Gel@CQDs, the removal rates of eosin Y by both Gel@CQDs-60 and Gel@CQDs-85 are reduced.

[0042] The low reaction temperature (60℃) of Gel@CQDs-60 resulted in fewer covalent bonds in the carbon quantum dots, and most of them were lost during post-processing, leading to a low carbon quantum dot loading and consequently a sharp decline in the degradation performance of eosin Y.

[0043] The high reaction temperature (85℃) of Gel@CQDs-85 may have increased the polymerization rate of the hydrogel, affecting its pore structure. With fewer pores, the dye diffusion rate is slow, which in turn affects the degradation performance of eosin Y.

[0044] The segmented temperature control method provided by this invention is key to preparing high-efficiency composite photocatalysts. First, the reaction is carried out at a low temperature of 60°C for 20 minutes to ensure stable polymerization and prepare a hydrogel substrate with a regular pore structure. Then, the reaction is carried out at a high temperature of 80°C for 6 hours, which allows the hydroxyl and carboxyl groups on the surface of carbon quantum dots to attack the pre-introduced epoxy groups in the hydrogel framework through affinity addition. This results in a more complete reaction, the formation of covalent bonds, and the prevention of carbon quantum dot detachment, which greatly improves the stability of the composite photocatalyst and the loading of carbon quantum dots.

[0045] 2. Cyclic stability The hydrogel-based composite photocatalyst Gel@CQDs extracted from the sample was soaked in deionized water for 12 hours, washed, and then used for the next cycle experiment.

[0046] After each cycle, the removal rate of eosin Y by Gel@CQDs is calculated as follows: Figure 11 .

[0047] from Figure 11The results show that after nine cycles, Gel@CQDs still exhibit excellent catalytic performance, maintaining a removal rate of over 90% for eosin Y. This indicates that Gel@CQDs possesses good stability and reusability, demonstrating significant potential in the treatment of industrial wastewater containing organic pollutants.

[0048] 3. Catalytic specificity Using aqueous solutions of eosin Y (100 mg / L), methyl orange (100 mg / L), methylene blue (100 mg / L), malachite green (100 mg / L), or rhodamine B (20 mg / L) as samples, the hydrogel-based composite photocatalysts Gel@CQDs (1 cm × 1 cm × 0.5 cm) prepared earlier were added to them. One hydrogel-based composite photocatalyst was added to every 10 mL of sample. Catalytic degradation was carried out at room temperature under sunlight irradiation. After 80 min, the hydrogel-based composite photocatalyst was removed from the sample, and the concentrations of eosin Y, methyl orange, methylene blue, rhodamine B, or malachite green in the sample were detected. The removal rates of eosin Y, methyl orange, methylene blue, rhodamine B, or malachite green were calculated.

[0049] The calculated removal rates of different organic dyes by the hydrogel-based composite photocatalyst Gel@CQDs are shown in the figure. Figure 12 .

[0050] from Figure 12 As can be seen, Gel@CQDs has good removal performance for common organic dyes (eosin Y, methyl orange, methylene blue, rhodamine B, malachite green), with a removal rate of over 90%.

[0051] It should be noted that the above embodiments are merely examples for clearly illustrating the present invention, and are not intended to limit the implementation of the present invention. Those skilled in the art can make other variations or modifications based on the above description. It is impossible to exhaustively list all possible implementations here. All obvious variations or modifications derived from the technical solutions of this invention are still within the scope of protection of this invention.

Claims

1. A method for preparing a hydrogel-based recyclable composite photocatalyst, characterized in that, Includes the following steps: (1) Using shelled fruit and vegetable residues as raw materials, nitrogen elements are doped by adding a polymer nitrogen source and carbon quantum dots are synthesized by hydrothermal method; (2) Dissolve acrylamide, hydroxyethyl methacrylate, glycidyl methacrylate, N,N-methylenebisacrylamide and potassium persulfate in deionized water in a ratio of 20 mmol: 0.5 mmol: 0.8 mmol: 0.08 mmol: 0.03 mmol: 10 mL, add carbon quantum dots and mix well; (3) Pour the mixture into a mold, seal it, heat it in a 60°C water bath for 20 min, and then raise the temperature to 85°C and react for 6 h; (4) The obtained composite hydrogel is soaked and washed with deionized water.

2. The method for preparing the hydrogel-based recyclable composite photocatalyst according to claim 1, characterized in that, In step (1), the shelled fruit and vegetable residues are cherry pits, walnut shells, peach pits, mango pits, coconut shells, durian shells, peanut shells, or melon seed shells.

3. The method for preparing the hydrogel-based recyclable composite photocatalyst according to claim 1, characterized in that, In step (1), the polymer nitrogen source is polyacrylonitrile, polyacrylamide, polymethacrylamide or polyvinylpyridine.

4. The method for preparing the hydrogel-based recyclable composite photocatalyst according to claim 1, characterized in that, In step (1), the hydrothermal reaction temperature is 200°C and the reaction time is 16h.

5. The method for preparing the hydrogel-based recyclable composite photocatalyst according to claim 1, characterized in that, In step (4), the deionized water is replaced every 8 hours for a total of 3 times.

6. A hydrogel-based recyclable composite photocatalyst, characterized in that, It is prepared by the method described in any one of claims 1 to 5.

Citation Information

Patent Citations

  • Hydrogel-based composite photocatalyst and preparation method thereof

    CN120268419A

  • Thermal initiation hydrogel deep purification device and process

    CN121851234A